Runestone images and visual communication in Viking Age Scandinavia - Stern, Marjolein (2013)
The aim of this thesis is the visual analysis of the corpus of Viking Age Scandinavian memorial stones that are decorated with figural images. The thesis presents an overview of the different kinds of images and their interpretations. The analysis of the visual relationships between the images, ornamentation, crosses, and runic inscriptions identifies some tendencies in the visual hierarchy between these different design elements. The contents of the inscriptions on runestones with images are also analysed in relation to the type of image and compared to runestone inscriptions in general. The main outcome of this analysis is that there is a correlation between the occurrence of optional elements in the inscription and figural images in the decoration, but that only rarely is a particular type of image connected to specific inscription elements.